1991
DOI: 10.1111/j.1432-1033.1991.tb16114.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing the catalytic sites of triosephosphate isomerase by 31P‐NMR with reversibly and irreversibly binding substrate analogues

Abstract: We have explored the degree of independence of the two catalytic centers, interactions between the catalytic centers and the subunit-subunit contact sites, and different conformations of triosephosphate isomerase (TPI), by simultaneously employing irreversibly (covalent) and reversibly binding substrate analogues and monitoring their 31P-NMR resonances. 3-Chloroacetol phosphate (CAP) was bound to the active site by reaction with Glu165. The resulting, inactive (CAP-TPQ2 complex exhibited two distinct 31P-NMR r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Loop 3 of one subunit projects between loops 1 and 4 of the other subunit; in this The slopes were then plotted against DTNB or MMTS concentrations, and the apparent rate constants ((, standard error) for the reaction were calculated from these slopes. arrangement, the side chain of cysteine 14 (Figure 4), which is part of loop 1 (residues [14][15][16][17][18][19], becomes closely packed within the core of loop 3 (residues 66-79). Indeed, in the two monomers of TcTIM, there are 12 and 13 atoms at a distance of less than 4 Å from the sulfur of the interface cysteine 14 (Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…Loop 3 of one subunit projects between loops 1 and 4 of the other subunit; in this The slopes were then plotted against DTNB or MMTS concentrations, and the apparent rate constants ((, standard error) for the reaction were calculated from these slopes. arrangement, the side chain of cysteine 14 (Figure 4), which is part of loop 1 (residues [14][15][16][17][18][19], becomes closely packed within the core of loop 3 (residues 66-79). Indeed, in the two monomers of TcTIM, there are 12 and 13 atoms at a distance of less than 4 Å from the sulfur of the interface cysteine 14 (Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that the tetramer is an enzyme with only two catalytically competent sites. In this connection, it is relevant to point out that TIM dimers, in which one of its two catalytic sites has been poisoned with a covalently linked inhibitor, express 50% of its maximal activity without important changes in Km,45, 46 indicating that the catalytic sites of two monomers work independently. However, Biemann and Koshland47 reported that a protein with two potential binding sites exhibited Michaelis–Menten behavior with a Hill coefficient of 1 and that, nonetheless, the protein expressed what they called half of the site reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Although each identical subunit carries an independent catalytic site, TIM is active in the dimeric form (except in some hyperthermophilic bacteria, where its functional form is tetrameric). However, cooperativity or allostery has not been observed between the two active sites (1). Each subunit (with 251 residues in TcTIM) adopts the TIM-barrel topology, in which the active site is located at the C-terminal end of the b-barrel.…”
Section: Introductionmentioning
confidence: 99%